Prevalence Of Refractive Errors In Patients Attending A General Eye Opd Myopia Hypermetropia Astigmatism - Waseem, Muhammad; Zeeshan Tahir, Muhammad; Khan, Jehanzeb; Rafiq, Muhammad; Hamza, Syed Amir; Sultan, Maria (Journal of Neonatal Surgery, 2025)
Background: Across the globe, myopia, hypermetropia, and Astigmatism are widespread forms of impaired vision. Luckily, they can all be corrected. However, these vision problems can heavily affect lower-income populations where affordable and timely corrective measures and screenings are less accessible. Identifying and monitoring the frequency of these vision problems among patients visiting a general eye OPD is critical to ensuring timely detection, prescribing appropriate spectacles, and designing public health initiatives to eliminate preventable vision impairment. Objectives: To determine the frequency and patterns of vision impairments among patients attending a general ophthalmology outpatient department and to assess their association with key demographic factors, particularly age and sex. Methodology: This was a cross-sectional study of 100 participants seen in general eye outpatient departments. Informed consent was received from the patients, after which they were asked a series of demographic and ocular history questions. Visual acuity was assessed using a Snellen visual acuity chart, followed by an objective and subjective refraction with an autorefractor. Based on the spherical equivalents, refractive errors were classified as myopia, hypermetropia, and Astigmatism. Those who had a history of corneal clouding, eye trauma, prior eye surgeries, retinal pathology, or retinal surgeries were removed from the study. SPSS 24 was used for data analysis. For the quantitative variables, means and standard deviations were determined. Associations for the categorical variables were determined using the chi-square statistic. Results: A total of 100 individuals participated in the study (54 males and 46 females), with a mean age of 32.8 ± 13.6 years. Refractive errors were detected in 72% of the cohort. Myopia constituted the most prevalent refractive condition (34%), followed by astigmatism (24%) and hyperopia (14%). A statistically significant association was observed between age and the presence of refractive errors (p < 0.05), whereas no significant relationship was identified between refractive error status and sex (p = 0.42). The majority of participants consented to the use of corrective spectacles following refraction. Conclusion: The findings indicate that refractive errors constitute a substantial proportion of presentations in general ophthalmology outpatient settings, highlighting the ongoing burden of correctable visual impairments. Routine vision screening, coupled with timely provision of corrective lenses, remains essential for reducing preventable visual difficulties and improving overall ocular health outcomes